ESTIMASI TAIL VALUE AT RISK SAHAM BLUE CHIPS MENGGUNAKAN COPULA ALI-MIKHAIL-HAQ - Candrasuari, Ni Luh Putu Diah Ayu; Sumarjaya, I Wayan; Sari, Kartika (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
When making investments, investors definitely want high returns with low risk. However, high returns are usually accompanied by high risks and vice versa. Value at Risk (VaR) and other measurement tools help manage risk. VaR measures possible losses. However, VaR has weaknesses, thus Tail Value at Risk (TVaR) can be used to evaluate the likelihood of larger losses than VaR. Copula can be used in risk management because it does not require normal distribution assumptions so it is well applied to financial data. The purpose of this research is to use the Ali-Mikhail-Haq copula to estimate TVaR value of blue chip stock portfolios, including those of BRI, BCA, and Bank Mandiri. Data used is the closing price of daily stocks for the period Jan 1 2021 to Jun 30 2023. The results of calculating TVaR value at the 90%, 95%, and 99% confidence level of the combination of BMRI and BBRI stocks are 0,0574; 0,0668; dan 0,0807. At a confidence level of 90%, 95% and 99% TVaR value of the combination of BMRI and BBCA stocks is 0,0569; 0,0669; dan 0,0886. The combination of BBRI and BBCA stocks resulted in TVaR at 90%, 95% and 99% confidence levels are 0,0238; 0,0283; 0,0376.